The effect of H2S and NaCl concentration on hydrogen permeation in high strength low alloy carbon steel C110. (17th February 2022) - Liu, Lianlian; Case, Raymundo
ABSTRACT: The sulphide stress cracking of high strength low alloy (HSLA) carbon steel C110 is related to the hydrogen absorption process. The objective of this research is to evaluate the effect of adsorbed H2 S and Cl − on hydrogen permeation in C110, by studying the responses of hydrogen permeation current and characteristic inductance under environment with different H2 S activities and NaCl concentrations using electrochemical methods, including hydrogen permeation method and electrochemical impedance spectroscopy (EIS). The hydrogen permeation current measured in Devanathan–Stachurski cell suggests that the enhance effect of the adsorbed H2 S on the hydrogen absorption follows an adsorption isotherm behaviour as a function of H2 S activity in solution. The inductive response of EIS under different H2 S activities shows consistency with hydrogen permeation results. The EIS results also indicate that the coverage of H2 S was suppressed by Cl − . A good correlation about the effect of adsorbed Cl − is found between inductive response and hydrogen permeation current.